Dual-functional copper oxide nanofluids for transformer: Synergistic enhancement of antimicrobial and insulating properties - Haidan Lin; Lijie Xu; Qunying Yu; Jiachang Guo; Dan Liu; Daiyong Yang; Jingyao Luan; Junbo Liu; Feilong Yi (AIP Advances)
Oil in transformer insulation systems critically safeguards grids, yet microbial contamination catastrophically compromises dielectric integrity, threatening grid resilience worldwide. To address this dual challenge of biocontamination and insulation degradation, we engineered bifunctional copper oxide nanofluids (CuO NFs) through crystallographic tailoring and surface charge optimization. Two dominant actinomycetes (Mycoplana and Rothia), isolated from operational transformers, achieved up to 98.19% and 96.32% inactivation rates when exposed to CuO NFs, coupled with a 1.62-fold increase in AC breakdown voltage compared to base oil, owing to the designed monoclinic-phase CuO nanoparticles (+20.14 ± 1.5 mV) that disrupted microbial integrity via electrostatic adhesion and reactive oxygen species (ROS) generation, which is the first demonstration of nanoscale ROS-mediated antimicrobial mechanisms in oil-immersed insulation systems. This work provides a robust strategy for the development of bifunctional NFs that mitigate microbial contamination and enhance insulating properties.